Conformity And Loneliness in Ruth Ozeki’s A Tale For The Time Being: An Analysis Of Social Influence And Psychological Impact - Josephine, J. Alisha (International Journal of Psychosocial Rehabilitation, 2024)
The article, “Conformity and Loneliness in Ruth Ozeki’s A Tale for the Time Being: An Analysis of Social Influence and Psychological Impact”explores the theme of conformity in Ruth Ozeki’s novel A Tale for the Time Being, examining how social influence impacts the characters, particularly the protagonist, Naoko Yasutani (Nao). Conformity is analyzed as a form of social influence that compels individuals to change their beliefs or behaviors to align with group norms. This change can result from both real and imagined pressures, such as bullying, teasing, and societal expectations. Nao, who experiences severe depression and loneliness, exemplifies the negative consequences of such social pressures. The novel highlights Nao’s struggles with identity, cultural displacement, and the lack of peer and familial support, all contributing to her sense of isolation. Additionally, the article delves into the psychological effects of conformity on Nao’s family members, particularly her father, Haruki Yasutani #2, who grapples with suicidal thoughts. The influence of societal norms and economic pressures on middle-aged men in Japan, leading to a high rate of suicides, is also discussed. The narrative underscores the importance of guidance and support, as seen through the transformative role of Nao’s great-grandmother, Jiko, a Zen Buddhist nun, who helps Nao and her father find meaning and strength in their lives. Ultimately, the article illustrates how Ozeki’s novel portrays the interplay between social conformity and individual psychological distress, and how characters can overcome these challenges through personal growth and supportive relationships.